2020
DOI: 10.1021/acs.jmedchem.9b01882
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Peroxisome Proliferator-Activated Receptor Delta (PPARδ): A Medicinal Chemistry Perspective

Abstract: One of the three subtypes of the peroxisome proliferator-activated receptor (PPAR) functioning as a transcription factor is the PPARβ or PPARδ. PPARδ is crucial to pathophysiological processes, including metabolic disorders, liver diseases, and cardiovascular diseases. In the past, the clinical development of PPARδ-selective agonist drugs has been stalled due to potential safety-related issues. Despite the elusiveness of such a drug, efforts continue in developing drugs that target PPARδ due to advances in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 164 publications
1
20
0
Order By: Relevance
“…30 One of the three subtypes of the PPAR functioning as a transcription factor is the PPARδ that are essential in several biological functions. 31 PPARδ is a key player in cardiac energy production, angiogenesis, and particularly in cancer progression. 32 A previous study reported that GW0742 (a PPARδ agonist) significantly reduced the mortality rate and inhibited inflammatory response in a mouse model of gut ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 One of the three subtypes of the PPAR functioning as a transcription factor is the PPARδ that are essential in several biological functions. 31 PPARδ is a key player in cardiac energy production, angiogenesis, and particularly in cancer progression. 32 A previous study reported that GW0742 (a PPARδ agonist) significantly reduced the mortality rate and inhibited inflammatory response in a mouse model of gut ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator‐activated receptors (PPARs), ligand‐activated transcription factors, belong to the nuclear hormone receptor superfamily, which have been suggested to regulate the expression of genes involved in different aspects of lipid redistribution, inflammation, and cardiac energy production 30 . One of the three subtypes of the PPAR functioning as a transcription factor is the PPARδ that are essential in several biological functions 31 . PPARδ is a key player in cardiac energy production, angiogenesis, and particularly in cancer progression 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Other reports suggest that GW501516 improves skeletal muscle mass in mouse models of muscular dystrophy [106] but has no effect on muscle mass in rats [107]. Furthermore, trials with GW501516 were discontinued due to preclinical data showing rapid induction of cancer in multiple organs [108]. Mitobridge (Boston, MA, USA) and Astellas (Tokyo, Japan) announced that their PPARδ agonist ASP0367 (also known as MA-0211), which is being developed for the treatment of primary mitochondrial myopathies, has recently been granted fast track designation by the U.S. Food and Drug Administration (FDA) ( Table 2).…”
Section: Exercise Mimeticsmentioning
confidence: 99%
“…PPARα or PPARγ agonist drugs, such as fibrates or thiazolidinediones (TZDs), have been widely employed for lipid and glycemic control [ 3 , 4 ]. On the other hand, no PPARδ agonists have been approved for clinical use [ 5 ]. However, recent studies have demonstrated that the full activation of these receptors is associated with unwanted effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, no PPARδ agonists have been approved for clinical use [ 5 ]. However, recent studies have demonstrated that the full activation of these receptors is associated with unwanted effects [ 5 , 6 ]. To overcome these issues, the concept of selective PPAR modulators (SPPARMs) with a superior balance of efficacy and safety has been proposed [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%